Severe epigastric pain following a birthday party. - REYNOLDS, JOHN; RAVI, NARAYANASAMY (My University, 2013)
Epigastric pain is a very common symptom which can be caused by a wide range of clinical conditions. A 28 year old male presented to our clinic with new onset severe epigastric pain. As part of the routine work up for pain of this nature, we proceeded to upper gastrointestinal endoscopy. A toothpick was found lodged in the antral gastric wall with a resulting inflammatory mass abutting the free edge. It was removed successfully with full resolution of symptoms, however a review of the literature shows that ingested toothpicks can cause major morbidity.
PUBLISHED
Keywords: Epigastric pain